Information systems - Baltzan, Paige; Phillips, Amy (Amy L.) (New York McGraw-Hill/Irwin, 2011)
Business driven information systems; Essentials of information systems; Enterprise information systems; Developing information systems.
Includes bibliographical references and index.
Keywords: Information technology -- Management; Electronic commerce; Business -- Computer programs; Hệ thống thông tin; Thương mại điện tử